Virtual Environments in the Mathematics Teaching-Learning Processes in High School - Pillajo-Yugcha, Manuel (2021)
The virtual learning classroom for the teaching of Mathematics in secondary school helps students improve their academic performance. Thus, the experimental group showed better progress than the control group, in which the difference was 0.14 points at the beginning of the process while at the end of the intervention it varied 2.22 points between the two groups. Through the means, the experimental group advanced from 4.78 points to 7.93 points, a variation of 3.15 points. The control group that participated in traditional teaching advanced from 4.64 points to 5.71 points, a variation of 1.07 points.